The political economy of democratic transitions - Haggard, Stephan; Kaufman, Robert R. (Princeton University Press, 1995)
Since the 1970s there has been a widespread movement from authoritarian to democratic rule among developing countries, often occuring against a backdrop of severe economic crises and the adoption of market-oriented reforms. This book analyzes this relationship, addressing a variety of questions.